Forearm muscle activation, ulnar nerve at the elbow and forearm fatigue in overhand sports - Wang, L.-H.; Lo, K.-C.; Jou, I.-M.; Su, F.-C. (Sports Biomechanics, 2020)
This study examined the morphologic changes of the ulnar nerve in different elbow positions by ultrasonography and the effects of fatigue on forearm muscle control during overhand movements. We enrolled 12 tennis players who performed flat serves and 15 baseball pitchers who performed fastball pitching. The motion capture was conducted with 14 reflective markers attached on anatomic landmarks of the participant for tennis serve and baseball pitching data collection. The distance from the nerve to the medial condyle between the tennis players and baseball pitchers showed significant differences (p = 0.006) as the elbow flexed to 90°. The differences are due to the baseball player`s repetitive pitching motion while such motion does not apply to tennis player. Activity of the extensor carpi radialis (ECR) during the cocking phase in the tennis serves showed significant differences (p = 0.022) between the nonfatigued and fatigued states; the maximal value was observed in the fatigued state. The significant increase in the ECR activity in the fatigued state might be responsible for grasp-and-release activities and maintaining the wrist joint stability when performing overhand movements. Forearm fatigue influenced their overhand motion ability in accurate ball control, although it did not decrease the ball speed.